Desain Karakter Maskot untuk Branding Perpustakaan Universitas Berbasis Budaya Akademik: Studi Kasus Universitas Dinamika - Setya Putri Erdiana; Evi Farsiah Utami; Jadeth Desak Tirani Palupi Fisa (MDP Student Conference, 2026)
Within higher education institutions, university libraries serve not only as information centers and learning resources but also as representations of academic values, intellectual culture, and institutional identity. However, in the digital era, libraries face challenges including declining student visits, shifts in information-seeking behavior toward digital platforms, and perceptions of libraries as rigid and less relevant to younger generations. These conditions highlight the need for adaptive and human-centered visual communication strategies to strengthen emotional engagement with users. This study employed a qualitative method through observation, interviews, and conceptual analysis combined with the Yuru-Chara mascot design framework, including message formulation, naming, visual development, and visibility strategies. The design process resulted in a mascot named Chilla, inspired by the characteristics of the chinchilla and developed using a futuristic anthropomorphic robotic approach. The mascot was implemented across various media to enhance visibility and support library branding.